Light-responsive self-assembly of a cationic azobenzene surfactant at high concentration. Issue 40 (1st October 2020) - Blayo, Camille; Kelly, Elaine A.; Houston, Judith E.; Khunti, Nikul; Cowieson, Nathan P.; Evans, Rachel C.
Abstract : A cationic azobenzene photosurfactant (AzoTAB) forms self-assembled structures with long-range order and optical anisotropy at high concentrations. These high-concentration mesophases are lost or disrupted with UV irradiation. Abstract : The formation of high-concentration mesophases by a cationic azobenzene photosurfactant is described for the first time. Using a combination of polarised optical microscopy and small-angle X-ray scattering, optically anisotropic, self-assembled structures with long-range order are reported. The mesophases are disrupted or lost upon UV irradiation.